Factors Affecting Behavior for Preventing Covid-19 Infection When Working on Employees During A Pandemi at Puskesmas Balai Agung, Sekayu District in 2021 - Rizka Muliani; Ririn Noviyanti Putri; Heru Listiono; Sutriyati; Nurrahmah Romadhona (Science Midwifery, 2022)
COVID-19 is a disease caused by the Novel Coronavirus (2019-nCov) or SARS-CoV-2. The highest cases were recorded in Sekayu District, where there were 811 positive confirmed cases, 14 deaths and 711 recovered cases. For an addition of 12 positive confirmed cases. Cases of COVID-19 infection in Indonesia, including cases of health workers and non-health workers exposed to COVID-19 infection, continue to increase in health care facilities. From this data, researchers are interested in researching "Factors Influencing Behavioral Prevention of COVID-19 Infection While Working for Employees During a Pandemic at the Balai Agung Health Center, Sekayu District in 2021". This study is an analytic study using a cross sectional approach, which involves the independent variables (knowledge, attitudes, gender, availability of hygiene facilities and availability of PPE) and the dependent variable (COVID-19 infection prevention behavior) collected at the same time. The sample research in this study used a non-random sampling method with a total sampling technique of 91 respondents. There is a relationship between knowledge and availability of cleaning facilities with COVID-19 infection prevention behavior while working for employees during the pandemic at the Balai Agung Health Center, Sekayu Subdistrict in 2021. It is expected to improve the quality and quantity of facilities and infrastructure that can protect employees working in health care facilities from exposure to the COVID-19 virus and can determine programs and policies to improve the quality of preventing COVID-19 infection for employees at the Puskesmas.